(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Main purpose of this research is to create the new reference method of determining the freeze-thaw resistance of concrete that is characterized by small labor input, high efficiency and a wide application scope. The offered method is based on measurement of long strength by nondestructive method. During this research, the theoretical analysis of concrete's specimen dependence on freeze-thaw resistance and energy, which is emitted by a specimen during destruction, has been carried out. Freeze-thaw resistance of a specimen is calculated as the mathematical relation of these energies, and the freeze-thaw resistance of concrete is calculated as an arithmetic mean value across specimens. To prove the method correctness it was realized on 10 concrete specimens. Age of specimens cosolidation is 88 days. Speciments of concrete mortar were prepared using a mix of portland cement 400 (12,3%), sand of dimentions 0.6-5 mm (24,7%), granite macadam of dimentions 5-20 mm (55,4%) and water (7,4%). Freeze-thaw resistance such mortar was determed earlier by method, approved national standard specification, it was equal 105 cycles. According dimentions by new offered method freeze-thaw resistance such mortar is equal 107 cycles and its confidence interval is equal 5,4 (probability P = 0,95). Therefore, spread of results could be casual and the offered method is correct.